Performance analysis of vacuum cooling integrated ice thermal energy storage system in maintaining Malaysia's indoor thermal comfort conditions - Chong Jin Yang; Mohd Rashdan Isa (Case Studies in Thermal Engineering)
This research investigates the relationship between water volume, cooling rate, and thermal insulation in a vacuum cooling integrated ice thermal energy storage (ITES) system through computational fluid dynamics (CFD) simulations, experimental work, and Internet-of-Things (IoT) integration. CFD simulations explored the solidification process with varying water volumes and the melting process with different insulation materials, including nickel, aluminum, and copper. The results demonstrated that larger water volumes were harder to cool due to high latent heat, while nickel provided the best insulation performance. Experimental findings confirmed that water volume is inversely proportional to the cooling rate, with the lowest water level achieving the lowest final temperature in the cooling material production system while nickel is best used as insulation in cooling system. The highest water volume showed a higher COP due to its greater mass and energy output. Lastly, an IoT system, developed using Python and Freeboard software, was integrated into the system to show that IoT automation integration could further optimize energy efficiency and maximize system productivity. Overall, the results highlight the promising potential of the vacuum cooling ITES system for cooling applications and could satisfy thermal comfort requirements in Malaysia.